An investigation of doping of SnO2 by ion implantation and application of ion-implanted films as gas sensors - Rastomjee, C; Dale, R; Schaffer, R; Jones, F; Egdell, R; Georgiadis, G; Lee, M; Tate, T; Cao, L (1996)
Thin films of SnO2 were doped with 90 keV ions of Nb, Sb and Bi at a dose of 3 × 1016 ions cm-2. The implanted films were characterized by X-ray and ultraviolet photoemission spectroscopy, Auger depth profiling and sheet resistance measurements. Sb produces the most dramatic reduction in sheet resistance and is unique in introducing a sufficient concentration of electrons into the Sn 5s conduction band to be observable by photoemission. The response of the resistance of Sb-doped films to pulses of CH4, CO and H2O in a flow of synthetic air was investigated over a range of concentrations and temperatures. The films display relatively poor selectivity in their sensor response. By contrast, the more highly resistive Bi-doped films show marked selectivity towards CO relative to CH4 in sensor applications.